Marine Climate of Russian Coastal Territories Public Health Aspects of Biological Adaption - Tarasov, Andrei Vyacheslavovich; Rakhmanov, Rofail Salykhovich (Cham : Springer International Publishing : Imprint: Springer, 2023)
The monograph was written based on the material of the post-doctoral thesis prepared under the supervision of Prof. Dr. Rakhmanov and it has been translated from its original version in Russian. It presents a comprehensive analysis of the process of biological adaptation and adaptation capacity of the population to the marine climate of Russia's North, the Black and Caspian Sea regions and the Baltic Sea coast. The authors explore different biological reactions to adaptation and offer their classification depending on the type of climate. Special attention is given to the prevention of prenosological conditions and diseases typical of coastal areas. Evidence suggests that the human body has a remarkable capacity to adapt to a range of climatic and weather conditions through a variety of targeted adaptation measures.
Chapter 1: Introduction -- Chapter 2: Climate and weather: impact on the body -- Chapter 3: Climatic norms, definition periods. Methods for determining the areas of biological comfort/discomfort -- Chapter 4: Adaptation to marine climate -- Chapter 5: Influence of weather and climatic conditions on health Adaptation to the marine climate of Russian regions -- Chapter 6: Non-specific prevention of pre-disease states and diseases when adapting to a maritime climate -- Chapter 7: Conclusion.
Keywords: Environmental geography; Public health; Climatology; Integrated Geography; Public Health; Climate Sciences